Library Supported Open Access Funds: Criteria, Impact, and Viability - Click, Amanda B.; Borchardt, Rachel (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2019)
Objective – This study analyzes scholarly publications supported by library open access funds, including author demographics, journal trends, and article impact. It also identifies and summarizes open access fund criteria and viability. The goal is to better understand the sustainability of open access funds, as well as identify potential best practices for institutions with open access funds.Methods – Publication data was solicited from universities with open access (OA) funds, and supplemented with publication and author metrics, including Journal Impact Factor, Altmetric Attention Score, and author h-index. Additionally, data was collected from OA fund websites, including fund criteria and guidelines.Results – Library OA funds tend to support faculty in science and medical fields. Impact varied widely, especially between disciplines, but a limited measurement indicated an overall smaller relative impact of publications funded by library OA funds. Many open access funds operate using similar criteria related to author and publication eligibility, which seem to be largely successful at avoiding the funding of articles published in predatory journals.Conclusions – Libraries have successfully funded many publications using criteria that could constitute best practices in this area. However, institutions with OA funds may need to identify opportunities to increase support for high-impact publications, as well as consider the financial stability of these funds. Alternative models for OA support are discussed in the context of an ever-changing open access landscape.